2016
DOI: 10.1039/c5ra26675k
|View full text |Cite
|
Sign up to set email alerts
|

Germanium and phosphorus co-doped carbon nanotubes with high electrocatalytic activity for oxygen reduction reaction

Abstract: Germanium and phosphorus co-doped carbon nanotubes (Ge–P-CNTs) were prepared by a simple and scalable approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 53 publications
(54 reference statements)
1
14
0
Order By: Relevance
“…The peak at 29.9 eV is attributed to pure Ge and other Ge chemical status. The main peak at 30.9 eV (55.66 atom %) is assigned to the C−Ge bonds, corresponding to the Ge‐doped carbon materials . The peaks at 31.4 and 32.0 eV can be ascribed to the oxidation state Ge (i. e. GeO) .…”
Section: Resultsmentioning
confidence: 99%
“…The peak at 29.9 eV is attributed to pure Ge and other Ge chemical status. The main peak at 30.9 eV (55.66 atom %) is assigned to the C−Ge bonds, corresponding to the Ge‐doped carbon materials . The peaks at 31.4 and 32.0 eV can be ascribed to the oxidation state Ge (i. e. GeO) .…”
Section: Resultsmentioning
confidence: 99%
“…S10 online), Ge, N and P were distributed uniformly on the rGO substrate. We also found that the N-Ge (398.1 eV) [7], P-Ge (134.1 eV) [4], P-C (132.4 eV) [12] and C-N bonds (288.7 eV) [13] from the XPS data for Ge-N-P-rGO ( Fig. S11 online).…”
mentioning
confidence: 60%
“…She et al [7] synthesized Ge and N co-doped graphene materials and proved their higher ORR performances experimentally and theoretically. Li et al [4] confirmed that Ge and P co-doped carbon nanotubes showed enhanced ORR catalytic activity and long-term durability. Unfortunately, the work function values of the co-doped samples were relatively large due to the obvious bandgap around Fermi level, making the electron unfavorable to transfer from the carbon surface to the vacuum.…”
mentioning
confidence: 97%
See 2 more Smart Citations